ANALISIS KESIAPAN BRIDGING SIMRS DAN V-CLAIM DI RUMAH SAKIT PRATAMA KOTA YOGYAKARTA - Salim, Marko Ferdian; Syakira, Imtinan Nasywa; Putri, Edvy Permata; Janah, Friska Miftachul (Jurnal Informasi Kesehatan Indonesia (JIKI), 2023)
Background: Hospital Information System (SIMRS) and Virtual Claim (V-Claim) are information systems used by hospitals in providing services. However, the different systems between SIMRS and V-Claim will have an impact on the effectiveness and efficiency of patient services, for example the patient registration process. Yogyakarta City Primary Hospital is conducting bridging between SIMRS and V-Claim so it is necessary to know the readiness level of the bridging system.Subjects and Method: This research method used a mixed methods with an exploratory design at the Yogyakarta City Primary Hospital in June-August 2022. This research was started with qualitative research and then continued with quantitative. Collecting data using interview techniques, observation, and questionnaires.Results: The SIMRS and V-Claim bridging systems have been successfully implemented at Yogyakarta Pratama Hospital with the support of man, money, machine, material, and method aspects that are well integrated with each other. The TRL measurement results show that the level of readiness for implementing the bridging system at the Yogyakarta City Pratama Hospital is at level 8.Conclusion: The SIMRS and V-Claim bridging systems have been successfully implemented at Yogyakarta Primary Hospital. Improving the Yogyakarta Pratama Hospital IT team to make repairs and improvements to TRL indicators that have not reached the maximum up to TRL level 9.